Citarum Authority Agency as the Commitment of the Government in the Conservation of Water Resources to Realize the System of Environmental-Based Water Management - Suwari Akhmaddhian (Jurnal Dinamika Hukum, 2019)
Water resources management requires the support of all parties involved in the commitment to jointly maintain sustainable and beneficial water resources and requires a focused and comprehensive institution so that the benefits of water availability are felt by the community. The goal is to analyze the Institutional Management of the Citarum Watershed; and Effectiveness of Government Policy in Conservation of Water Resources to Realize the System of Environmental-Based Water Management. The results of the study are that government policies in Citarum must be equipped with more comprehensive regulations, especially strengthening the permits for housing development must pay attention to the concept of conservation of water resources; Government commitment is strengthened, namely 1 (one) policy in the management of the Citarum River, namely the Citarum Authority Agency that replaces the function and role of agencies that have been managing the Citarum River, then with 1 (one) water resource management.Keywords: government; citarum authority agency; conservation of water resources.